A caring interview: Polar questions, epistemic stance and care in examinations of eligibility for social benefits. (August 2019) - Ekström, Mats; Bruhn, Anders; Thunman, Elin
Based on conversation analysis, this study investigates central practices in what is defined as a caring interview, in the context of welfare administration. Caring refers to (1) a helpful interviewing in reformulations of questions, taking interviewees' difficulties to answer into consideration; (2) a caring attitude in the framing of questions, showing understanding of clients' circumstances and (3) professional's enactment of expertise in assessments of clients' disabilities and care needs. Data include a corpus of 43 recorded interviews in which officials at the Swedish Social Insurance Agency interview clients who have applied for benefits. The study adds to research on interactional sensitivity, polar questions and epistemic stance in institutional interaction. The study shows how the interviewer prioritizes confirming polar questions, takes responsibilities of knowing into account and reduces the epistemic gap to the interviewee in practices of a caring interview. This makes the interviewing markedly different from standardized and bureaucratic interviewing.